Key factors deterring women's engagement with skilled birth attendants in three districts of Timor—Leste. A qualitative descriptive study. (December 2019) - King, Rosemary; Jones, Linda
Highlights: Widespread poverty and women's workloads reduce women's access to SBA. Other barriers are lack of overall infrastructure, poor amenity and dearth of services. Poorly skilled and resourced SBA contribute to women's lack of confidence in services. Timor-Leste's antecedents contribute to women's lack of power and access to SBA. Abstract: Objective: To describe the barriers to women's access to maternity services in three districts of Timor-Leste. Research design/setting: Focused ethnography with data collection methods commensurate with a qualitative research design. Setting and participants: Data was collected in three districts in Timor-Leste. Participants included seventeen stakeholders, health professionals and managers providing skilled birth attendance (SBA) in Timor-Leste and thirty women who have given birth and are competent to give consent. Findings: Access to SBA services is seriously impeded by poor roads and lack of transportation, the poor condition and amenity of services, restricted hours of opening, the lack of availability of skilled SBA professionals and medical resources. Participants also commented upon the lack of privacy and multiple caregivers. Timorese patriarchal family structures, intergenerational decision-making and cultural attitudes towards reproductive health information and services potentially reduce women's access to reproductive health services. Conclusion: This data provides a comprehensive record of the multiple structural barriers to women's access to SBA services. The modified AAAQA framework provides categories and an organisational structure to these barriers to SBA services. Implications for practice: Maternity care in Timor-Leste is extremely poorly resourced. Midwives and other SBA will need to provide innovative low cost solutions if they are to consistently provide respectful culturally safe midwifery care. This includes the provision of privacy and a one to one midwifery relationship `with woman'. In addition, many women are unable to access SBA, where possible the MoH can consider strategies to improve the provision of SBA services to women birthing in community.